Studentsâ Perceptions of History Fieldwork ICSS in Relation to Vision 2020 in Malaysia - Salleh, Mohamad Johdi; Madin, Abu Bakar (ASPENSI in Bandung, Indonesia, 2009)
ABSTRACT: The Malaysian government and the agencies had allocated and spent millions of Ringgits to preserve and decorate the national heritage such as the museums, archives, gallery, artefacts, sites, and other historical remains. These are became major tourist attraction which indirectly inculcated knowledge and enhanced appreciation upon the practices of multi-ethnic and multi-cultural Malaysian. Thus, this paper discusses a study on the studentsâ perceptions of fieldwork approaches to history of the Integrated Curriculum for Secondary Schools (ICSS) Malaysia in relation to the challenges of Vision 2020. The study was conducted in various types of schools in Perak and Terengganu which involved about eight hundred students. The result of the study shows a high relation concerning the studentsâ perceptions of fieldwork approaches of history and the challenges of Vision 2020. It is hoped that more students would benefit from this core subject of the lower and upper secondary levels, ICSS Malaysia, towards the development of the twenty-first millennium first class human capital of Malaysian and 1-Malaysia nation.KEY WORDS: national heritage and integration, studentsâ perceptions, Integrated Curriculum for Secondary Schools, and Vision 2020 Malaysia.Â Â About the Authors: Mohamad Johdi Salleh, Ph.D. is a Senior Lecturer at the Institute of Education, International Islamic University of Malaysia (IIUM), Jalan Gombak, 53100 Kuala Lumpur, Malaysia; and Abu Bakar Madin is a Lecturer at the Sultan Hassanal Bolkiah Institute of Education, University of Brunei Darussalam (UBD), Bandar Seri Begawan, Negara Brunei Darussalam. E-mail: johdisalleh@gmail.comHow to cite this article? Salleh, Mohamad Johdi & Abu Bakar Madin. (2009). âStudentsâ Perceptions of History Fieldwork ICSS in Relation to Vision 2020 in Malaysiaâ in TAWARIKH: International Journal for Historical Studies, Vol.1(1) October, pp.83-96. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 5, 2009); Revised (September 8, 2009); and Published (October 28, 2009).